2012
DOI: 10.1523/jneurosci.4494-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neural Broadening or Neural Attenuation? Investigating Age-Related Dedifferentiation in the Face Network in a Large Lifespan Sample

Abstract: Previous studies have found that cortical responses to different stimuli become less distinctive as people get older. This age-related dedifferentiation may reflect the broadening of the tuning curves of category-selective neurons (broadening hypothesis) or it may be due to decreased activation of category-selective neurons (attenuation hypothesis). In this study, we evaluated these hypotheses in the context of the face-selective neural network. Over 300 participants, ranging in age from 20 to 89 years, viewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
148
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(183 citation statements)
references
References 25 publications
31
148
4
Order By: Relevance
“…This network-specific mechanism is also supported by a recent study which demonstrated that age-related dedifferentiation reflects distinct processes in different brain areas (Park et al, 2012). Specifically, while age-related dedifferentiation in the fusiform face area was mainly driven by increased activation to houses, dedifferentiation in the extended face network reflected decreased activation to faces (Park et al, 2012). Grady et al (2006) propose that a shift in the balance between neuronal activity and recruitment during rest and task, respectively, may result in behavioral phenotypes of cognitive aging.…”
Section: Relations To Theories Of Cognitive Agingsupporting
confidence: 70%
See 1 more Smart Citation
“…This network-specific mechanism is also supported by a recent study which demonstrated that age-related dedifferentiation reflects distinct processes in different brain areas (Park et al, 2012). Specifically, while age-related dedifferentiation in the fusiform face area was mainly driven by increased activation to houses, dedifferentiation in the extended face network reflected decreased activation to faces (Park et al, 2012). Grady et al (2006) propose that a shift in the balance between neuronal activity and recruitment during rest and task, respectively, may result in behavioral phenotypes of cognitive aging.…”
Section: Relations To Theories Of Cognitive Agingsupporting
confidence: 70%
“…Further studies integrating various structural and functional indices of the aging brain are highly needed, and may reveal novel age-related patterns not easily detected by univariate and unimodal studies (Groves et al, 2012). This network-specific mechanism is also supported by a recent study which demonstrated that age-related dedifferentiation reflects distinct processes in different brain areas (Park et al, 2012). Specifically, while age-related dedifferentiation in the fusiform face area was mainly driven by increased activation to houses, dedifferentiation in the extended face network reflected decreased activation to faces (Park et al, 2012).…”
Section: Relations To Theories Of Cognitive Agingmentioning
confidence: 78%
“…This subsample includes at least 30 participants in each decade of the sampled age range and represents individuals who performed the complete series of seven fMRI runs [e.g., Chan et al, 2014; Kennedy et al, 2015; Park et al, 2012, 2013; see Fig. 1].…”
Section: Methodsmentioning
confidence: 99%
“…As individuals grow older, there appears to be a decrease in the specificity of activation of neural modules in response to different kinds of stimuli, such as target vs. non-target letters or numbers, images of faces vs. non-faces, and cued vs. non-cued locations (Curran, Hills, Patterson, & Strauss, 2001; Hahn, Wild-Wall, & Falkenstein, 2011; Kenemans, Smulders, & Kok, 1995; Looren de Jong, Kok, & van Rooy, 1988; Lorenzo-Lopez, Amenedo, Pazo-Alvarez, & Cadaveira, 2007; Park et al, 2012). This age-related loss of neural specialization has been indexed by comparing neural responses to different stimulus types and by measuring changes in the distribution of neural activity recruited to carry out task demands (Cabeza, Anderson, Locantore, & McIntosh, 2002; Lorenzo-Lopez et al, 2007).…”
Section: Introductionmentioning
confidence: 99%